2014
DOI: 10.3233/ch-131771
|View full text |Cite
|
Sign up to set email alerts
|

The passage of a hemodialysis filter affects hemorheology, red cell shape, and platelet aggregation

Abstract: We investigated the influence of the passage of a hemodialysis filter on red blood cells (RBCs), platelets, and hemorheological parameters. After one hour of hemodialysis, blood was drawn from 15 patients immediately ahead and behind the dialysis filter. RBCs were fixed for morphological analysis. Blood viscosity was measured with a Couette viscometer (LS-30, Contraves), RBC aggregation with a Myrenne aggregometer, platelet aggregation in flowing whole blood and in platelet rich plasma. The passage of the hemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Therefore, significantly increased levels of CD62P and P10 expressions can induce platelet activation and coagulation. It has been reported that HD could contribute to the increased levels of whole blood viscosity, plasma viscosity, red cell assembling index, as well as promoted platelet activation . CD62p and P10 levels could be elevated after HD treatment owing to the promoted effects of HD on platelet activation; therefore, HD treatment should be employed with assisted drug treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, significantly increased levels of CD62P and P10 expressions can induce platelet activation and coagulation. It has been reported that HD could contribute to the increased levels of whole blood viscosity, plasma viscosity, red cell assembling index, as well as promoted platelet activation . CD62p and P10 levels could be elevated after HD treatment owing to the promoted effects of HD on platelet activation; therefore, HD treatment should be employed with assisted drug treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Reinhart et al reported the change of hemorheology of the circulation after hemodialysis with the result of increased hematocrit and increased plasma and whole blood viscosity after the hemodialysis was done, due to the influence of the hemodialysis passage. 9 Amit Nautiyal et al reported a case of patient with Purtscher-like retinopathy with multiple myeloma. 8 In their case, hyperviscosity from multiple myeloma was mentioned to be the cause of Purtscher-like retinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7] The pathogenesis of hyperviscosity and vascular autoregulation are now under investigation. 8,9 Recently, computational fluid dynamic simulation software has shown the role of wall shear stress as a new mechanism in the development of Purtscher's and Purtscher-like retinopathies. 10 Treatment of Purtscher-like retinopathy is to correct the causative systemic pathology and for ocular treatment, observation is usually advised.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, blood viscosity can be influenced by blood transfusions in sepsis [7]. Finally, knowing that dialysis increases blood viscosity and alters RBC rheology [15,16] patients who require renal replacement therapy may present further altered hemorheology. Piagnerelli et al concluded in their RBC rheology in sepsis review that blood viscosity is influenced mainly by plasma visosity, shear rate, deformability and aggregation [8].…”
Section: Blood Viscositymentioning
confidence: 99%